2010
DOI: 10.1007/s00586-010-1609-1
|View full text |Cite
|
Sign up to set email alerts
|

An MRI study of psoas major and abdominal large vessels with respect to the X/DLIF approach

Abstract: Extreme/direct lateral interbody fusion (X/DLIF) has been used to treat various lumbar diseases. However, it involves risks to injure the lumbar plexus and abdominal large vessels when it gains access to the lumbar spine via lateral approach that passes through the retroperitoneal fat and psoas major muscle. This study was aimed to determine the distribution of psoas major and abdominal large vessels at lumbar intervertebral spaces in order to select an appropriate X/DLIF approach to avoid nerve and large vess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 19 publications
2
39
0
2
Order By: Relevance
“…To reduce risk of vascular injury, lateral approaches have been established [28,29]. The ''extreme'' or ''direct lateral'' transpsoas approaches have increased in popularity, partly because of the natural distance to the abdominal vessels [19,30,38,40]. However, numerous studies have shown neurologic injury resulting from this transpsoas approach, which is in close anatomic proximity to the lumbar nerve plexus [2,16,18,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…To reduce risk of vascular injury, lateral approaches have been established [28,29]. The ''extreme'' or ''direct lateral'' transpsoas approaches have increased in popularity, partly because of the natural distance to the abdominal vessels [19,30,38,40]. However, numerous studies have shown neurologic injury resulting from this transpsoas approach, which is in close anatomic proximity to the lumbar nerve plexus [2,16,18,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Regev confirmed that the safe surgical corridor decreases from 47.9% at L1-L2 to 13.1% at L4-L5 of the anterior-posterior diameter of the vertebra [8]. Additionally, surgeons should consider the risk of vascular injuries due to surgical proximity to major vessels, especially in right-sided approaches [18]. However, these studies were anatomic cadaveric studies which may or may not be reflective of in vivo operating conditions.…”
Section: Discussionmentioning
confidence: 99%
“…14,21,33 The transpsoas approach does, however, pose risk to neural structures of the lumbar plexus as they course through the psoas. 2,12,13,15,21 The large muscle belly of the psoas and overlap of the iliac crest make access to the L4-5 disc difficult and eliminate access to the L5-S1 disc.…”
mentioning
confidence: 99%